Microsoft Azure development cookbook : over 70 advanced recipes for developing scalable services with the Microsoft Azure platform /: over 70 advanced recipes for developing scalable services with the Microsoft Azure platform. (2014) - Freato, Roberto; Mackenzie, Neil
No abstract available